2014
DOI: 10.1210/jc.2014-1690
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Synthesis and Vitamin D Action

Abstract: Data from our human primary testicular cell culture model suggest that vitamin D plays a major role in male steroidogenesis in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 39 publications
4
36
0
Order By: Relevance
“…1,25-dihydroxyvitamin D has both genomic and non-genomic effects on Sertoli cells in the testes leading to increased testosterone steroidogenesis in cell culture models. [7,8] However, supplemental trials in adult men have shown inconsistent findings with one study showing vitamin D supplementation modestly increased serum T levels[16] and another study finding null results. [13] Therefore, whether treating vitamin D deficiency can improve a low T state directly is inconclusive at this time, and our data does not support a relationship beyond shared risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,25-dihydroxyvitamin D has both genomic and non-genomic effects on Sertoli cells in the testes leading to increased testosterone steroidogenesis in cell culture models. [7,8] However, supplemental trials in adult men have shown inconsistent findings with one study showing vitamin D supplementation modestly increased serum T levels[16] and another study finding null results. [13] Therefore, whether treating vitamin D deficiency can improve a low T state directly is inconclusive at this time, and our data does not support a relationship beyond shared risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] The active metabolite of vitamin D, 1,25-dihydroxyvitamin D, regulates a number of enzymes involved in steroid hormone production, including both adrenal steroid hormones and sex hormones, as well as sex hormone signaling. [7,8]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VDR-knockout female mice show reproductive defect due to impaired follicle maturation [14], which is possibly due to the accumulation of androgens via UGT2B15 defectiveness, as found in the present study. The VDR also plays a role in regulating testicular androgen production [29]. VDR ligands suppress UGT2B15 expression in the prostate [4,11].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence also exists for vitamin D to play a role in fertility and steroidogenesis. However, randomized controlled trials are warranted to further investigate this possible effect [57,58,59]. In summary, again current evidence is scarce and definite conclusions on the role of vitamin D in non-skeletal diseases cannot be drawn at the moment; future studies might provide evidence on positive extraskeletal effects of vitamin D.…”
Section: Extraskeletal Diseases and Vitamin Dmentioning
confidence: 99%